2022
DOI: 10.1136/bmjopen-2021-050337
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal association of thyroid-stimulating immunoglobulin levels with clinical characteristics in thyroid eye disease

Abstract: ObjectivesThe clinical course of thyroid eye disease (TED) is heterogeneous and predicting patients who may develop the severe sequelae of the disease is difficult. In this study, we evaluated the longitudinal association between changes in serum thyroid-stimulating hormone (TSH) receptor antibody (TRAb) levels and course of disease activity and severity over time.DesignThis was a multicentre, prospective, observational study.SettingFifteen tertiary care oculoplastic service centres in Korea.ParticipantsSevent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 38 publications
1
5
0
Order By: Relevance
“…We not only analyzed the clinical features of patients with moderate-to-severe GO but also performed a comparison with mild type at initial examination and proposed predictive scores for moderate-to-severe type GO. Associations between the factors included in the scores and GO were demonstrated in previous studies [ 8 , 9 , 23 , 24 , 25 ]. However, this is the first study to present a predictive score with these factors for use at initial examination in Korea.…”
Section: Discussionsupporting
confidence: 64%
“…We not only analyzed the clinical features of patients with moderate-to-severe GO but also performed a comparison with mild type at initial examination and proposed predictive scores for moderate-to-severe type GO. Associations between the factors included in the scores and GO were demonstrated in previous studies [ 8 , 9 , 23 , 24 , 25 ]. However, this is the first study to present a predictive score with these factors for use at initial examination in Korea.…”
Section: Discussionsupporting
confidence: 64%
“…36 Ko et al recently reported that TSI was significantly correlated with the NOSPECS score in a cohort of Korean patients. 37 Jeon et al reported a cross-sectional study included 101 patients with TED and found the TSI level was higher among males patients and smokers, and the TSI level was inversely correlated with the duration of ocular symtoms. 38 Ponto et al reported that TSI level can help to identify patients with DON of recent onset requiring urgent treatment.…”
Section: Discussionmentioning
confidence: 99%
“…26,27 Ponto et al 28 reported that TSI was associated with activity and severity of TED disease. The inflammatory phase of TED reportedly correlates with changes in measured TSI levels, indicating that serial measurements of TSI levels may be an adjunct in assessing the clinical inflammatory activity of TED 29 ; Ko et al 30 demonstrated that TSI and TBII levels decrease 1 year after TED diagnosis, whereas disease activity measured using clinical activity score (CAS) decreases mainly in the first 6 months, demonstrating that the measurement of serum TSI and TBII levels may help evaluate TED prognosis. In addition, the change in TSI levels in TED patients who underwent medical and surgical interventions was found to be positively correlated with quality of life assessed by the Graves Orbitopathy Quality of Life questionnaire.…”
Section: Trabmentioning
confidence: 99%
“…21 In addition, interperson differences in TBII levels were associated with several clinical scores including CAS, no signs or symptoms, only signs, soft tissue involvement, proptosis, extraocular muscle involvement, corneal involvement, sight loss (NO-SPECS) score, and proptosis over time. 30 Nevertheless, elevated TSI levels have been found to be better associated with clinically active TED than TBII levels. 28,36 Moreover, when comparing TSI and TBII assays' ability to identify dysthyroid and compressive optic neuropathy, TSI was found to be more sensitive and specific.…”
Section: Tbiimentioning
confidence: 99%
See 1 more Smart Citation